2022
DOI: 10.3390/jfb13040260
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Platinum Nanoparticles for Biomedical Applications

Abstract: The diverse biological properties of platinum nanoparticles (PtNPs) make them ideal for use in the development of new tools in therapy, diagnostics, and other biomedical purposes. “Green” PtNPs synthesis is of great interest as it is eco-friendly, less energy-consuming and minimizes the amount of toxic by-products. This review is devoted to the biosynthesis properties of platinum nanoparticles based on living organisms (bacteria, fungi, algae, and plants) use. The participation of various biological compounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 202 publications
0
6
0
Order By: Relevance
“…The green synthesis of the Centella asiatica -mediated SeO-NPs showed a color change from black to brown, which can be compared with a similar study, wherein the synthesis of Se-NPs mediated by Ceropegia bulbosa Roxb extract showed a color change from yellow to ruby red [ 21 ]. Hence, various biomolecules found in plants, such as proteins, enzymes, flavonoids, terpenoids, phenolic compounds, and organic acids, among other compounds, are involved in the synthesis and packaging of nanoparticles [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The green synthesis of the Centella asiatica -mediated SeO-NPs showed a color change from black to brown, which can be compared with a similar study, wherein the synthesis of Se-NPs mediated by Ceropegia bulbosa Roxb extract showed a color change from yellow to ruby red [ 21 ]. Hence, various biomolecules found in plants, such as proteins, enzymes, flavonoids, terpenoids, phenolic compounds, and organic acids, among other compounds, are involved in the synthesis and packaging of nanoparticles [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…After long‐term exposure of P. aeruginosa to platinum nanoparticles, it was found that oprD was upregulated while mexEF‐oprN was downregulated, facilitating the intracellular accumulation of antibiotics and reducing the resistance of P. aeruginosa to imipenem and ciprofloxacin (Zhou et al., 2023 ). Since platinum nanoparticles are widely utilized in medical applications (Mikhailova, 2022 ), the combination of platinum nanoparticles and traditional antibiotics provides a promising approach to combat antibiotic‐resistant P. aeruginosa . Probiotics are used as dietary supplements which provide multiple health benefits (Ali et al., 2023 ).…”
Section: Anti‐resistance By Modulating Antibiotic Influx and Efflux M...mentioning
confidence: 99%
“…Obtaining AgNPs is of interest not only as a method and assessment of the level of reducing power, but also as an independent biotechnological process of creating a product (nanoparticles), which can find wide practical applications due to having anticancer effect, antibacterial, antioxidant, anti-inflammatory and anti-hyperglycemic activity [18][19][20][21][22][23][24][25], as well as anti-quorum sensing potential [26]. Advances of such "green" silver, zink, gold, platinum, nickel, aluminum and iron nanoparticles are widely researched [27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%